Determinants of active pulmonary tuberculosis in Ambo Hospital, West Ethiopia - Tenna Ephrem; Bezatu Mengiste; Frehiwot Mesfin; Wanzahun Godana (AOSIS, 2015)
Objectives: The aim of this study was to determine factors associated with active pulmonary tuberculosis seen in cases in Ambo Hospital, Ethiopia. Design: A facility-based prospective case-control study. Setting: Patients attending Ambo Hospital from 01 December 2011 to 29 March 2012. Participants: The sample included 312 adult patients attending Ambo Hospital. The main outcome measure was presence of active pulmonary tuberculosis (TB). Explanatory measures: Age, gender, occupation, educational status, marital status, place of residence, patient history of TB, family history of TB, human immunodeficiency virus (HIV) infection, smoking, alcohol intake, khat chewing, body mass index (BMI), employment, diabetes, history of asthma, previous history of worm infestation, history of hospitalisation, number of adults living in the household (HH), person per room, housing condition. Results: A total of 312 study participants, including 104 active pulmonary tuberculosis (PTB) cases (cases) and 208 non-active PTB cases (controls), were recruited for the present study. Having one or more family member with a history of TB (OR = 4.4; 95% CI: 1.50-12.90), marital status (OR = 7.6; 95% CI: 2.2-12.6), male gender (OR = 3.2; 95% CI: 1.4-7), rural residence (OR = 3.3; P = 0.012), being a current or past smoker (OR = 2.8; 95% CI: 1.1-7.2), BMI < 18.5 (OR = 2.1; 95% CI: 1.03-4.2), HIV infection (OR = 8.8; 95% CI: 2.4-23.8) and a history of worm infestation (OR = 6.4; 95% CI: 2.6-15.4) remained significant independent host-related factors for active PTB. Conclusion: Patients who came from a compound with more than two HHs were more likely to develop active PTB than those who came from a compound with only one HH. Those who lived in houses with no windows were more likely to develop active PTB than those who lived in houses with one or more windows, had a family history of TB, lived in rural areas. Sex of the patient was a predicting factor. Not being the owner of the house was significantly more associated with active PTB. Measures taken to reduce the prevalence and burden of active PTB should consider these determinant factors.